O ECA nos anos iniciais do ensino fundamental - Tezani, Thaís Cristina Rodrigues [UNESP]; Bortoletto, Évelyn Bianco [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project "the ECA in the initial years of the elementary school" lists the teaching with research and with the extension, because it articulates the contents of various disciplines of Education course with practice in elementary schools regarding the rights of children based on the Statute of the child and adolescent. Therefore, the work has as its main objective to provide the proper understanding and application of the Statute of the child and adolescent (ECA) in the early years of elementary school, getting rid of myths and prejudices that hinder the necessary understanding of its purpose and importance by the students. The momentum for implementation of the interventions used thematic workshops that encompass various procedures and features such as games, jokes, songs, videos, discussions, specific didactic material on the ECA, in order to facilitate the learning process of a law for students of the early years of elementary school. Is based on theoretical assumptions of historical-cultural aspects, seeking to carry out concrete actions, linked to research and teaching. However, due to the reduction of grants and zero budget there was appropriateness of methodology, being that in 2015 we are conducting construction and adaptation of teaching material that will be forwarded to the schools.

O Projeto “O ECA nos anos iniciais do ensino fundamental” relaciona o ensino com a pesquisa e com a extensão, pois articula os conteúdos de várias disciplinas do curso de Pedagogia com a prática nas escolas de ensino fundamental no que tange os direitos das crianças com base no Estatuto da Criança e do Adolescente. Sendo assim, o trabalho tem como objetivo principal proporcionar a devida compreensão e aplicação do Estatuto da Criança e do Adolescente (ECA) nos anos iniciais do ensino fundamental, livrando-se de mitos e preconceitos que prejudicam o necessário entendimento de sua finalidade e importância pelos alunos. A dinâmica para realização das intervenções utiliza-se de oficinas temáticas que englobam diversos procedimentos e recursos, como jogos, brincadeiras, músicas, vídeos, debates, material didático específico sobre o ECA, com o intuito de possibilitar o processo de aprendizagem de uma Lei por alunos dos anos iniciais do ensino fundamental. Baseia-se nos pressupostos teóricos da vertente históricocultural, buscando realizar ações concretas, articuladas com pesquisa e ensino. Entretanto, em virtude da redução das bolsas e do orçamento zerado houve adequação da metodologia, sendo que no ano de 2015 estamos realizando construções e adequações do material didático que será encaminha para as escolas.
Keywords: Statute of the child and adolescent; Early years of elementary school; Estatuto da Criança e do Adolescente; Anos iniciais do ensino fundamental